Probiotics May Have Beneficial Effects in Parkinson's Disease: In vitro Evidence - Magistrelli, Luca; Amoruso, Angela; Mogna, Luca; Graziano, Teresa; Cantello, Roberto; Pane, Marco; Comi, Cristoforo (Frontiers in Immunology, 2019)
Background: Parkinson’s disease (PD) is characterized by loss of dopaminergic neurons and intraneuronal accumulation of alpha-synuclein, both in the basal ganglia and in peripheral sites, such as the gut. Peripheral immune activation and reactive oxygen species (ROS) production are important pathogenetic features of PD. In this context, the present study focused on the assessment of in vitro effects of probiotic bacterial strains in PD patients versus healthy controls. Methods: we enrolled 40 PD patients and 40 matched controls. Peripheral blood mononuclear cells (PBMCs) were isolated and cultured with the following strains: Lactobacilli (salivarius, plantarum, acidophilus, rhamnosus) and Bifidobacteria (breve and lactis). Modulation of the in vitro release of the major pro- (Tumor Necrosis Factor-alpha and Interleukin-17A and 6) and anti-inflammatory (Interleukin 4 and 10) cytokines by PBMCs was investigated, as well as the production of ROS. Furthermore, we assessed the ability of probiotics to protect membrane integrity, counteract the growth of bacteria, such as Escherichia coli and Klebsiella pneumoniae and encode tyrosine decarboxylase genes (tdc). Results: All strains were able to inhibit inflammatory cytokines and ROS production in both patients and controls. The most striking results in patients were obtained with L. salivarius and acidophilus which significantly reduced pro-inflammatory and increased the anti-inflammatory cytokines (p<0.05). Furthermore, most strains determined restoration of membrane integrity and inhibition of Escherichia coli and Klebsiella pneumoniae overgrowth. Finally, we also showed that our strains do not carry tdc, which are known to decrease levodopa bioavailability. Conclusions: Probiotics exert promising in vitro results in decreasing pro-inflammatory cytokines, oxidative stress and bacterial overgrowth. In vivo longitudinal data are mandatory to support the use of bacteriotherapy in PD.